Computer Modelling of Supply Chain Management and Marketing Efficiency of Onion - Malaisamy, A.; Raswanthkrishna, M (New Advances in Business, Management and Economics Vol. 3, 2025)
Poor efficiency in the marketing channels and inadequate marketing infrastructure is believed to be the cause of not only high and fluctuating product prices but also too little of the consumer rupee realized by the farmer. To find out the supply chain management at the producer level, a total of 120 sample respondents were selected for this study, which included 60 farmers and 60 intermediaries were selected using a random sampling procedure during the year 2022-23. The results of the analysis of indices of marketing efficiency in the six marketing channels prevailing in three different markets are presented in Table 8 in the Tiruchi and Dindigul districts of Tamil Nadu. It could be inferred that the index of marketing efficiency was highest for Channel II of all three markets (Dindigul, Tiruchi), because of direct purchase of onion by retailers from commission agents. The market efficiency was found to be lowest in Channel I of the Tiruchi market with an index of 2.39 for small onion. A systematic package of practices in onion production will greatly improve productivity and enable the growers to reap maximum benefits.